11PMolecular determinants of interaction between glioblastoma CD133+ cancer stem cells and extracellular matrix. (7th November 2019) - Bryukhovetskiy, I S; Khotimchenko, Y; Shevchenko, V
Abstract: Background: Treatment of glioblastoma multiforme remains little effective due to the rapidly developing recurrence of the tumour, due to its high tumorigenic potential, resistance to chemoradiation therapy and increased dissemination of glioma stem cells (GSC). Molecular mechanisms of these cell interaction with extracellular matrix (ECM) are practically not studied. At present, it is also not clear the signalling of the ECM-receptor interaction (ECM-RI) differs for GSC and differentiated glioma cells (GDC). Methods: Using high-resolution proteomic mass spectrometry to study the determinant expression of the ECM-receptor interaction signalling cascade in cancer stem CD133+cells and differentiated CD133– glioblastoma cells. Results: 1990 proteins are identified, 18 of which are associated with the ECM-receptor interaction. Positive regulation of 10 proteins of signalling pathway of receptor interaction with ECM in CSCs (COL6A1, COL6A3, FN1, ITGA2, ITGA5, ITGAV, ITGB1, ITGB3, LAMB1, LAMC1) was discovered. More than double increase in the expression level of these proteins makes CSC proteome similar to the glioblastoma cells with aggressive phenotype. Increased expression levels of 4 proteins (FERMT2, LOXL2, HDAC2, FBN1), activating signalling in receptor interaction with ECM, indicates CSCs' highly invasive nature. The LOXL2 expression level was more than 9 times higher that allows using this protein as an important marker of CSCs and a very promising target for eliminating these cells. Conclusions: Important regularities are determined that could be used for the development of new approaches for detection of potential therapy targets of glioblastoma multiforme. Legal entity responsible for the study: Far Eastern Federal University of Russia. Funding: Ministry of Science and Higher Education of Russian (Agreement №14.584.21.0027 ID:RFMEFI58417X0027). Disclosure: All authors have declared no conflicts of interest.